Comparison of Breast Cancer Radiotherapy Techniques Regarding Secondary Cancer Risk and Normal Tissue Complication Probability – Modelling and Measurements Using a 3D-Printed Phantom - Vogel, Marc; Gade, Jonas; Timm, Bernd; Schürmann, Michaela; Auerbach, Hendrik; Nüsken, Frank; Rübe, Christian; Melchior, Patrick; Dzierma, Yvonne (Frontiers in Oncology, 2022)
Background: Radiotherapy after breast-conserving therapy is a standard postoperative treatment of breast cancer, which can be carried out with a variety of irradiation techniques. The treatment planning must take into consideration detrimental effects on the neighbouring organs at risk – the lung, the heart and the contralateral breast, which can include both short- and long-term effects represented by the normal tissue complication probability and secondary cancer risk. Patients and Methods: In this planning study, we investigate intensity modulated (IMRT) and three dimensional conformal (3D-CRT) radiotherapy techniques including sequential or simultaneously integrated boosts as well as interstitial multicatheter brachytherapy boost techniques of 38 patients with breast conserving surgery retrospectively. We furthermore develop a 3D-printed breast phantom add-on to allow for catheter placement and to measure the out-of-field dose using thermoluminescent dosimeters placed inside an anthropomorphic phantom. Finally, we estimate normal tissue complication probabilities using the Lyman-Kutcher-Burman model and secondary cancer risks using the linear non-threshold model (out-of-field) and the model by Schneider et al. (in field). Results: The results depend on the combination of primary whole breast irradiation and boost technique. The normal tissue complication probabilities for various endpoints are of the order: 1 – 2 % (symptomatic pneumonitis, ipsilateral lung), 2 – 3 % (symptomatic pneumonitis, whole lung), and 1 – 2 % (radiation pneumonitis grade ≥ 2, whole lung). The additional relative risk of ischemic heart disease ranges from +25% to +35%. In-field secondary cancer risk of the ipsilateral lung in left-sided treatment is around 50 per 10000 person-years for 20 years after exposure at age 55. Out-of-field estimation of secondary cancer risk results in approximately 5 per 10000 person-years each for the contralateral lung and breast. Conclusions: In general, 3D-CRT shows the best risk reduction in contrast to IMRT. Regarding the boost concepts, the brachytherapy is the most effective method in order to minimize normal tissue complication probability and secondary cancer risk compared to teletherapy boost concepts. Hence, the 3D-CRT technique in combination with an interstitial multicatheter brachytherapy boost is most suitable in terms of risk avoidance for treating breast cancer with techniques including boost concepts.